(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Advanced / Metastatic gastric cancer has a short survival prognosis despite many advances in treatment. In particular, in the group of elderly patients, with many comorbidities and poor performance status score, a specific treatment strategy is needed. Monochemotherapy is the preferred treatment. Therefore, our study aimed to evaluate the efficacy and safety of monochemotherapy in this group of patients. Methods: Retrospective study describing a series of cases. Patients with recurrent, advanced, metastatic gastric cancer who had not received previous systemic treatment were then treated with a monochemotherapy regimen with or without targeted therapy at the Department of Breast, Gastroenterology, Hepatology, and Urology, Ho Chi Minh City Oncology Hospital from January 1, 2023 to April 30, 2024. Results: The analysis included 58 patients (median age 65 years); 93% of patients had ECOG ≥1. 41.4% of patients had other comorbidities. 62.1% of patients were initially treated with TS-1, followed by Capecitabine (13.8%). The ORR and DCR were 18.9% and 55.1%, respectively. 32.8% received second-line and beyond therapy. Median PFS was 4 months and median OS was 5 months. Toxicities were mostly grade 1 and 2. The most common adverse events were anemia (32.8%), and nausea (31.1%). No deaths due to toxicity were recorded. No differences in survival were observed in different subgroups according to age, treatment regimen, or metastatic location. Conclusions: Monochemotherapy regimens may be a safe option for a special group of elderly patients, those with poor PS and multiple cormobidities.